1993
DOI: 10.1111/j.1476-5381.1993.tb13959.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of purine and pyrimidine nucleotides on the rat superior cervical ganglion

Abstract: 1 Using a grease-gap technique, we have investigated the effects of purine and pyrimidine nucleotides on the d.c. potential of the rat isolated superior cervical ganglion (SCG). 2 Of the purines tested, adenosine, adenosine 5'-triphosphate (ATP), P,y-methylene-adenosine 5'-triphosphate (P,y-MeATP) at up to 300 gM produced concentration-dependent hyperpolarizations, whereas 2-methyl-thio-ATP (2-Me.S.ATP) and a,p-methylene-ATP (a,,B-MeATP) depolarized ganglia. Of the pyrimidines tested, uridine 5'-triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…This hypothesis is supported by the observation that prolonged application of UTP produced a concentrationdependent depression of subsequent responses to UTP but not responses mediated by x,4-Me-ATP, potassium or adenosine. Both the present observations and the inability of selective P2-purinoceptor antagonists to antagonize depolarizations of the rat SCG by UTP (Connolly et al, 1993;Connolly & Harrison, 1994) strongly indicate that these rat SCG neurones possess pyrimidinoceptors and support the idea that pyrimidinoceptors exist within the nervous system. I thank Dr P.J.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…This hypothesis is supported by the observation that prolonged application of UTP produced a concentrationdependent depression of subsequent responses to UTP but not responses mediated by x,4-Me-ATP, potassium or adenosine. Both the present observations and the inability of selective P2-purinoceptor antagonists to antagonize depolarizations of the rat SCG by UTP (Connolly et al, 1993;Connolly & Harrison, 1994) strongly indicate that these rat SCG neurones possess pyrimidinoceptors and support the idea that pyrimidinoceptors exist within the nervous system. I thank Dr P.J.…”
supporting
confidence: 59%
“…Some evidence for the presence of distinct P2-purinoceptors and pyrimidinoceptors on sympathetic neurones has been obtained by use of P2-purinoceptor antagonists, suramin (Connolly et al, 1993), pyridoxalphosphate-6-azophenyl-2',5'-disulphonic acid (Connolly & Harrison, 1994) and reactive blue 2 (unpublished observations) which selectively antagonized a,4-Me-ATP but not UTP-evoked depolarizations of the rat superior cervical ganglion (SCG). In order to assess whether purine and pyrimidine 5'-nucleotides activate distinct receptors on the rat SCG the effects of desensitization by UTP or a,-Me-ATP on responses evoked by these nucleotides was determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast both a,-Me-ATP and UTP depolarized rat SCG neurones and depolarizations elicited by UTP were not antagonized, rather they were enhanced in the presence of either suramin (a Present address: Biomedical Sciences Division, Physiology Group, King's College, Strand, London WC2R 2LS. P2X-purinoceptor antagonist) or reactive blue 2 (a P2Y-purinoceptor antagonist) (see Connolly et al, 1993b;Connolly & Harrison, 1994 respectively). Recently it has been proposed that pyridoxal 5-phosphate-6-azophenyl-2',4'-disulphonic acid (PPADS) is a novel and selective antagonist of P2x-purinoceptors (Lambrecht et al, 1992;Ziganshin et al, 1993;McLaren et al, 1994) however, the effect of PPADS on UTP-mediated responses has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been proposed that neurones of the rat superior cervical ganglion (SCG) possess pyrimidinoceptors and that this preparation is a model tissue for the study of pyrimidinoceptors within the nervous system (Connolly & Harrison, 1993;Connolly et al, 1993b;Connolly, 1994a). This hypothesis was based upon the observation that there are distinct receptors that are activated by UTP but not by ATP or x, methylene adenosine 5'-triphosphate (m,-Me-ATP) (a selective P2X-purinoceptor agonist (Burnstock & Kennedy, 1985)).…”
Section: Introductionmentioning
confidence: 99%